Inventori fonem konsonan dialek Melayu Kuching Sarawak - Samasu, Saidatul Faiqah; Abdul Aziz, Adi Yasran (Persatuan Linguistik Malaysia, 2013)
The aim of this article is to review the previous study on the segment inventory of Kuching Sarawak Malay dialect. As shown in previous studies, differences was spotted in term of the number and status of segments inventory proposed. Research conducted by Asmah (2008) and Collins (1987) discovered 19 consonant phoneme in DMKS, in contrast to 20 consonant phoneme proposed by Madzhi (1988). These findings were based on structural approach that of assuming that phoneme is all sound segments produced from human articulator. To clarify this confusion, a study was conducted, implementing method of observation, secondary data analysis and first-hand knowledge of researcher as DMKS native speaker. This study utilized generative phonology approach. The analysis revealed that DMKS has 17 consonant segments, including /y/ and /?/ segments which considered non-phonemic in standard Malay language. The findings of the study has also dispensed derived segments [w], [j] and loan segments from DMKS consonant inventory which has been previously claimed as phoneme.